Don't Tell Me What to Do: Highly Restrictive Goals Promote Temptation Indulgence. (25th August 2015) - Buzinski, Steven G.; Price, Allison
Self-control is required when the pursuit of focal goals conficts with the desire to indulge in temptations. As such, the characteristics of one's focal goals may influence the likelihood of their attainment. The present work explored the hypothesis that highly restrictive goals increase the desire for, and the likelihood of indulging in, goal-damaging temptations. Highly restrictive goals can engender psychological reactance, a motivation to restore threatened freedom, by placing salient restrictions on the freedom to indulge in temptations. Consequently, one may indulge in those temptations in order to restore the threatened sense of freedom. Three experiments supported this hypothesis: Framing goals as highly restrictive caused greater desire for (Studies 1 and 2), and more behavioral indulgence in (Study 3), goal-damaging temptations. Theoretical and practical implications are discussed.